The Effect of the SALUD (Sadar Lalu Lintas AUD) Project on Improving Learning Outcomes of Early Childhood Diversity Dimension - Hendrica, Mega; Imamah (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study aims to analyze the application of the value of bhayangkara in the implementation of P5 reinforcement at Bhayangkari 01 Serang Kindergarten. Using associative methods and quantitative approaches, this study examines the relationship between the independent variable, namely the SALUD program, and the dependent variable, namely the emergence of learning outcomes on the value of bhayangkara. This study uses SPSS version 24 software to analyze numerical data obtained from assessment and observation sheets. The subjects of the study were early childhood children aged 4 to 6 years with a total of 60 children. This study is expected to provide an important contribution to the development of learning methods by involving parties outside the school to improve the value of bhayangkara. The hypothesis tested is that there is a positive and significant influence between the SALUD program and the indicator of the emergence of learning outcomes on the value of bhayangkara. This study was conducted at Bhayangkari 01 Serang Kindergarten in June - August 2024. The results of the bivariate analysis reported that the odds ratio (OR) 3.4; P value: 0.002 <0.05; 95% CI: 1.63 – 7.37. The interpretation of this result is that the SALUD program is able to increase the emergence of learning outcomes in the diversity dimension in Bhayangkari Kindergarten students 3 times higher and is statistically significant. Based on the results of the multivariate analysis, it is known that the SALUD program still has a significant effect on improving learning outcomes in Kemala Bhayangkari 01 Serang Kindergarten students p value 0.018 <0.05. This result remains significant even though there are differences in gender and age